Advantages of Heterotrophic Microalgae as a Host for Phytochemicals Production - Jareonsin, Surumpa; Pumas, Chayakorn (Frontiers in Bioengineering and Biotechnology, 2021)
Currently, most commercial recombinant technologies rely on host systems. However, each host has their own benefits and drawbacks, depending on the target products. Prokaryote host is lack of post-transcriptional and post-translational mechanisms, making them unsuitable for eukaryotic productions like phytochemicals. Even there are other eukaryote hosts (e.g. transgenic animals, mammalian cell, and transgenic plants), but those hosts have some limitations, such as low yield, high cost, time consuming, virus contamination, and so on. Thus, flexible platforms and efficient methods that can produced phytochemicals are required. The use of heterotrophic microalgae as a host system is interesting because it possibly overcome those obstacles. This paper presents a comprehensive review of heterotrophic microalgal expression host including advantages of heterotrophic microalgae as a host, genetic engineering of microalgae, genetic transformation of microalgae, microalgal engineering for phytochemicals production, challenges of microalgal hosts, key market trends, and future view. Finally, this review might be a directions of the alternative microalgae host for high-value phytochemical production in the next few years.